Low levels of sulfur and cobalt during the pre- and periconceptional periods affect the oocyte yield of donors and the DNA methylome of preimplantation bovine embryos - Nochi, Allice R. Ferreira [UNESP]; Vargas, Luna N.; Sartori, Roberto; Júnior, Roberto G.; Araújo, Davi B.; Figueiredo, Ricardo A.; Togawa, Roberto C.; Costa, Marcos M. C.; Grynberg, Priscila; Mendonça, Anelise S.; Kussano, Nayara R.; Pivato, Ivo; et al. (My University, 2022)
Maternal nutrition is critical in mammalian development, influencing the epigenetic reprogramming of gametes, embryos, and fetal programming. We evaluated the effects of different levels of sulfur (S) and cobalt (Co) in the maternal diet throughout the pre- and periconceptional periods on the biochemical and reproductive parameters of the donors and the DNA methylome of the progeny in Bos indicus cattle. The low-S/Co group differed from the control with respect to homocysteine, folic acid, B12, insulin growth factor 1, and glucose. The oocyte yield was lower in heifers from the low S/Co group than that in the control heifers. Embryos from the low-S/Co group exhibited 2320 differentially methylated regions (DMRs) across the genome compared with the control embryos. We also characterized candidate DMRs linked to the DNMT1 and DNMT3B genes in the blood and sperm cells of the adult progeny. A DMR located in DNMT1 that was identified in embryos remained differentially methylated in the sperm of the progeny from the low-S/Co group. Therefore, we associated changes in specific compounds in the maternal diet with DNA methylation modifications in the progeny. Our results help to elucidate the impact of maternal nutrition on epigenetic reprogramming in livestock, opening new avenues of research to study the effect of disturbed epigenetic patterns in early life on health and fertility in adulthood. Considering that cattle are physiologically similar to humans with respect to gestational length, our study may serve as a model for studies related to the developmental origin of health and disease in humans.
Keywords: Epigenetics; intergenerational inheritance; livestock